Protected yet unmanaged: insights into the ecological status of conservation priority stony reefs in Belgian waters based on the integrative use of remote sensing technologies - Montereale Gavazzi, Giacomo; Paoletti, Silvia; Podholova, Pavlina; Kapasakali, Danae-Athena; Kerckhof, Francis (Frontiers in Environmental Science, 2023)
Stony reefs are ecologically important, providing irreplaceable ecosystem services. These fragile environments are recognised as conservation priorities by all relevant global and European policies. Bottom-contacting fisheries are an important source of anthropogenic disturbance to the seafloor’s physical and ecological integrity having immediate and destructive consequences on stony reefs and compromising ecological functions. This study, aimed to assess the ecological status (community composition and functions) of two stony reef areas -Northwest and Hinder Banks study sites -in Belgian waters using multiple remote sensing tools. Insights on the study sites’ geomorphological context and fishing patterns were gained using echo-sounding and publicly available satellite data. Video-based benthic community data were assessed against the exposure to fishing pressure using a trait-based approach linked to the biotas’ resistance and recovery potential. In the Northwest study site, between 2019 and 2022 there was a significant decline in the abundance of benthic species classified with low resistance and recovery potential to trawling. Conversely, there was a notable increase in species with moderate scores. During the same period, this site experienced an eight-fold increase in fishing effort and the hydroacoustic data revealed the presence of several trawl-marks in 2022. Similar changes in benthic communities were observed in the Hinder Banks too. Here, the abundance of species with low resistance and recovery potential was significantly lower in locations that were geomorphologically exposed to trawling compared to sheltered ones. Exposed locations had a higher abundance of opportunistic species, with moderate to high scores. The presence of several trawl marks on the seafloor was observed in the exposed locations, corresponding to fishing hotspots identified in the satellite data. Trawling activities marginally impacted richness and total abundance, but negatively altered benthic functional composition. The findings of this study provide scientific evidence of the detrimental impact of bottom-contacting fisheries on conservation priority biotopes and argues against the coexistence of such activities with Marine Protected Areas. The results of our investigation are of interest to environmental managers for the adequate implementation of environmental legislation in the face of rapid and widespread anthropogenic changes.